The effect of extrusion conditions and the use of a compatibilizer in the crystallization of PBT/ABS blends - Ambrósio,José Donato (2013)
Poly(butylene terephthalate) (PBT)/ acrylonitrile-butadiene-styrene (ABS) terpolymer blends were prepared in a twin screw extruder and the use of methyl methacrylate-glycidyl methacrylate-ethyl acrylate (MGE) terpolymer as compatibilization additive was evaluated. The effect of different screw profiles and mixing conditions were evaluated on the crystallization of the blends. Differential scanning calorimetry (DSC) was used to evaluate melting and crystallization behaviors of the PBT/ABS blends. The binary PBT/ABS blend has shown a double melting peak when cooled at lower cooling rates, mainly due to its melt-recrystallization during the heating up step. ABS has not affected the melting characteristics of neat PBT. The presence of MGE, as a reactive compatibilizer, in the PBT/ABS blends has reduced its heat of fusion and has partially inhibited its melt-recrystallization under heating. As result, it has prevented the occurrence of double melting peak. The epoxy functional groups of the MGE may react in situ to the carbonyls and hydroxyls end groups of the PBT molecules, thereby hindering the mobility of PBT molecules during the crystallization process due to its grafting to the compatibilizer molecules. The melt mixed blends prepared at lower feeding rate have shown a higher degree of crystallinity for the PBT/ABS blend, probably due to degradation of PBT caused by longer residence time in the extruder. The highest shear stress imposed to the blends at higher screw speed increased the degree of crystallinity of PBT, also due to its degradation.